A Qualitative Investigation of Shopping Behavior of Customers at Bottom of the Pyramid. Issue 4 (8th August 2021) - Sharma, Bodh Raj; Gupta, Nikita
Abstract: In recent years, the " Bottom of the Pyramid " (BOP) market has become an attraction for researchers, business managers, and policymakers. Numerous researchers have contributed theoretically and empirically to the BOP literature, however, little focus is accorded to BOP customers' buying behavior. It is interesting to study the shopping behavior of BOP customers characterized by low disposable income, poor standard of living, and geographical isolation. Therefore, the present study aims to investigate the shopping behavior of BOP customers to identify the drivers and hindrances in the buying decisions. The study follows a qualitative approach by conducting in-depth personal interviews of 100 BOP customers visiting Vishal Mega Marts (VMMs) in a northern Indian city. The results indicate that BOP customers aspire for a better shopping experience like affluent customers, however, income constraint restricts them to buy superior brands. Indeed, BOP customers are persuaded by excessive discounts, gifts, coupons, peer influence, and seasonal offers by VMMs. The study provides implications for researchers, retailers, and policymakers.